Answer:
![\large\boxed{b=0}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7Bb%3D0%7D)
Step-by-step explanation:
![4b+6=2-b+4\qquad\text{combine like terms}\\\\4b+6=(2+4)-b\qquad\text{add}\ b\ \text{to both sides}\\\\5b+6=6\qquad\text{subtract 6 from both sides}\\\\5b=0\qquad\text{divide both sides by 5}\\\\b=0](https://tex.z-dn.net/?f=4b%2B6%3D2-b%2B4%5Cqquad%5Ctext%7Bcombine%20like%20terms%7D%5C%5C%5C%5C4b%2B6%3D%282%2B4%29-b%5Cqquad%5Ctext%7Badd%7D%5C%20b%5C%20%5Ctext%7Bto%20both%20sides%7D%5C%5C%5C%5C5b%2B6%3D6%5Cqquad%5Ctext%7Bsubtract%206%20from%20both%20sides%7D%5C%5C%5C%5C5b%3D0%5Cqquad%5Ctext%7Bdivide%20both%20sides%20by%205%7D%5C%5C%5C%5Cb%3D0)
The answer is B because if the result is 3/4 and the question is asking to the result then you would an equation.
Answer:
C
Step-by-step explanation:
Answer:
![y = 23.75x + 76.24](https://tex.z-dn.net/?f=y%20%3D%2023.75x%20%20%2B%2076.24)
Step-by-step explanation:
We want to rewrite
![y = 99.99 + 23.75(x - 1)](https://tex.z-dn.net/?f=y%20%3D%2099.99%20%2B%2023.75%28x%20-%201%29)
in the form
![y = ax + b](https://tex.z-dn.net/?f=y%20%3D%20ax%20%2B%20b)
We expand to get:
![y = 99.99 + 23.75x - 23.75](https://tex.z-dn.net/?f=y%20%3D%2099.99%20%2B%2023.75x%20-%2023.75)
Regroup similar terms:
![y = 23.75x - 23.75 + 99.99](https://tex.z-dn.net/?f=y%20%3D%2023.75x%20-%2023.75%20%2B%2099.99)
Simplify:
![y = 23.75x + 76.24](https://tex.z-dn.net/?f=y%20%3D%2023.75x%20%20%2B%2076.24)
This is now of the form
![y = ax + b](https://tex.z-dn.net/?f=y%20%3D%20ax%20%2B%20b)
where a=23.75 and b=76.24